KONTRIBUSI KELENTURAN PERGELANGAN TANGAN DAN POWER OTOT LENGAN DAN BAHU DENGAN KETERAMPILAN SERVIS ATAS PADA TEAM BOLA VOLI PUTRA SMA NEGERI 7 DURI KECAMATAN MANDAU KABUPATEN BENGKALIS - Angga Setiawan; Saripin '; Ni Putu Nita Wijayanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : Based on the researcher’s observation in SMAN 7 Mandau , the problem was the students’ serving skill was no maximal and the serve used to touch the net.The aim of the research was to know how big the contribution of of the wrist flexibility and arm muscle and shoulder power in serving skill for male volleyball team of SMA 7 Duri in Mandu, Bengkalis. The population of this research was The population of the research was fifteen male volleyball team of SMA 7 Duri in Mandau, Bengkalis. The technique of collecting data was total sampling because the population was not the big amount. The instrument of the research were the flexibility test to get the wrist flexibility, two hand medicine ball put to test the arm muscle and shoulder power, and the volleyball serving test to test the serving skill in volleyball. The data were analysed by using Product Moment Correlation and the contribution was analysed by using determinant coeficient. According to the researcher’s previous writing, it was concluded that the contribution of the wrist flexibility through serving skill was 31.25% and the contribution of arm muscle and shoulder power was 31.25%. In conclusion, the contribution of two variables in serving skill was 45.56%.Keywords : The wrist flexibility, arm muscle and shoulder power, serving skill